Analysis of the mediating effects of self-efficacy and self-control between physical activity and Internet addiction among Chinese college students - Du, Zhihao; Zhang, Xiuli (Frontiers in Psychology, 2022)
This study aims to analyze the relationship between self-efficacy, self-control and college students' physical activity and Internet addiction. It explores the roles of self-efficacy and self-control in physical activity and Internet addiction. And it further provides a theoretical basis for the treatment and improvement of Internet addiction among college students. This study employs the whole group sampling method. The questionnaire was conducted on 855 college students from five universities in three provinces using the Physical Activity Level Scale, the General Self-Efficacy Scale, the Self-Control Scale and the Chinese Internet Addiction Scale. The analysus yielded three main findings.⑴ A large amount of physical activity was helpful in reducing the symptoms of Internet addiction and the problematic status of each dimension among college students. ⑵A large or moderate amount of physical activity was helpful in enhancing college students' self-efficacy. Besides, a large amount of physical activity was likely to enhance college students' self-control. ⑶The condition of physical activity not only directly has the negative correlation with college students' Internet addiction but also influences college students' Internet addiction through two indirect ways: the mediating role of self-control and the chain mediating role of self-efficacy and self-control. These conclusions provide a deeper understanding of the protective factors of Internet addiction among Chinese college students.